La population de chamois (Rupicapra rupicapra) du Jura suisse est sur le point de décroître - Gauvain Saucy (VertigO)
This study examines the situation of the population of chamois Rupicapra rupicapra in the canton of Jura (Switzerland) in order to highlight a potential gap between the management of the species and its natural dynamics. In addition, the situation of the species in the canton of Jura is compared to its national situation. The chamois number in the canton of Jura is far from the carrying capacity of the habitat, and the current management of the species is about to induce a decrease in the population, as evidenced by annual removal rates exceeding annual growth rates. Hunting management contributes thus to the gap from the natural equilibrium. Action should be taken as soon as possible to reverse this trend.